2004
DOI: 10.1074/jbc.m406857200
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Rhodopsin into the Active Metarhodopsin II State Opens a New Light-induced Pathway Linked to Schiff Base Isomerization

Abstract: Rhodopsin bears 11-cis-retinal covalently bound by a protonated Schiff base linkage. 11-cis/all-trans isomerization, induced by absorption of green light, leads to active metarhodopsin II, in which the Schiff base is intact but deprotonated. The subsequent metabolic retinoid cycle starts with Schiff base hydrolysis and release of photolyzed all-trans-retinal from the active site and ends with the uptake of fresh 11-cis-retinal. To probe chromophore-protein interaction in the active state, we have studied the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 42 publications
2
55
1
Order By: Relevance
“…The changes must originate either from Meta-III or opsin. The latter was eliminated by following DHA attenuation over 24 h. The state of rhodopsin with highest magnetization transfer rate toward DHA decayed with a characteristic time of hours as it had been reported for the Meta-III-toopsin conversion (37). The opsin-induced attenuation of DHA was indistinguishable from DHA attenuation by dark-adapted rhodopsin.…”
Section: P St-mas Nmr On Ros-mentioning
confidence: 74%
“…The changes must originate either from Meta-III or opsin. The latter was eliminated by following DHA attenuation over 24 h. The state of rhodopsin with highest magnetization transfer rate toward DHA decayed with a characteristic time of hours as it had been reported for the Meta-III-toopsin conversion (37). The opsin-induced attenuation of DHA was indistinguishable from DHA attenuation by dark-adapted rhodopsin.…”
Section: P St-mas Nmr On Ros-mentioning
confidence: 74%
“…32 Other work suggests that both Glu 113 and Glu 181 are unprotonated and that both act as the PSB counterion, with Glu 181 dominating in the Meta I state. 33 We have simulated both Glu 113 and Glu 181 in their unprotonated states, and we find that structural changes occur that could lead to the PSB counterion switching from Glu 113 to Glu 181. The simulation shows that the salt bridge between the retinal PSB and Glu 113 breaks near t = 70 ns after photoisomerization and does not form again (Figs.…”
Section: Psb Counterion Switchmentioning
confidence: 93%
“…11,32,[54][55][56][57][58][59][60][61][62][63][64][65] This would involve a change in protonation states during the photocycle 33 and experimental work has confirmed that Glu 113 is the dark-state counterion and been suggestive, but not conclusive, that Glu 181 is active during the light-activated stages. 66,67 The simulation results are intriguing in suggesting that this counterion switch mechanism could be present as part of the relaxation mechanism of the protein to the retinal conformational change.…”
Section: Counterion Switchmentioning
confidence: 99%
“…Therefore, it is tempting to speculate that during molecular evolution of rhodopsins, vertebrate visual pigments including bovine rhodopsin acquired higher G protein activation ability through acquisition of the larger conformational change, a byproduct of which also resulted in abolishment of photoreversibility in the rhodopsins at the same time. Interestingly, metarhodopsin I, the precursor of the active state of bovine rhodopsin (metarhodopsin II), can be converted back to the dark state by subsequent light absorption (39). Comparison of conformation between metarhodopsin I and the active state of parapinopsin would provide a further evolutionary suggestion.…”
Section: Discussionmentioning
confidence: 99%